Diagnosis and management of eosinophilic granuloma of the jaw: a case report - Marcos Vinícius Mendes DANTAS; Paloma Beatriz Rosa Nunes de SOUZA; Marisa Aparecida Cabrini GABRIELLI (Faculdade São Leopoldo Mandic, 2019)
The eosinophilic granuloma is the most common form of the Langherans' cell histiocytosis. In the majority of cases it is represented by a unilocular osteolytic lesion which can occur in adults and children. It is an intraosseous destructive lesion characterized by the presence of vast numbers of eosinophils and histiocytes. It can be localized or multifocal. The tumor is more prevalent in the first two decades of life and tends to affect mandibular body and angle. Most frequent signs and symptoms are pain, swelling, ulceration, gingival necrosis, alveolar bone destruction with mobility and loss of teeth. Therapeutic interventions for this pathology are surgical curettage, local radiotherapy and chemotherapy. This article presents the case of a 9-year old patient who came in for treatment with facial swelling, pain, tooth mobility and intraoral ulcer in the vestibular sulcus of the right mandibular angle region. Imaging and incisional biopsy were obtained. After the histopathological examination confirmed the diagnosis of eosinophilic granuloma, the lesion was removed by curettage and a reconstruction titanium plate was inserted to avoid a pathological fracture. After 14 years of follow-up no recurrence was found and mandibular growth was not impaired. A discussion about this type of tumor is presented, based on the current literature.